Eid Mulud as a Determinant of Eid al-Fitr for the Community in Kidang Village, West Nusa Tenggara (NTB) - Rivaldi, Muhammad Haikal (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2024)
This research is motivated by the practice of determining the Eid al-Fitr holiday of the community in Kidang Village which is different from the government. Their determination is based on the understanding of Kyai Ratna which is known as the Eid mulud method. The difference in methods in determining this holiday is a very important issue to discuss because it is related to the worship of Muslims. Therefore, the purpose of this research is to find out how the method and the nature of Eid al-Fitr as a determinant of Eid al-Fitr in Kidang Village. This research is a field research with a qualitative approach. The data collection methods used are direct observation methods, unstructured interviews, and documentation, while the analysis methods used are qualitative descriptive analysis methods. Researchers found that the Eid mulud method is based on the hisab urfi of the rowot sasak calendar which has identical similarities with the hisab urfi of the Javanese Islamic calendar of the asapon system. This method is accurate in terms of urfi hisab because there is a determination of the age of the moon while in the contemporary hisab it is not accurate because there is a difference of 1 day caused by the absence of a day determination in the contemporary hisab. This method is not only inaccurate in terms of hisab, it is also inaccurate in terms of rukyah based on the results of ijtimak according to contemporary hisab.